Surgical Extirpation of Glomus Tumor from Rare Localization on the Upper Extremity - Jan Hrubý; Robert Novotný; Miroslav Špaček; Petr Mitáš; Jaroslav Hlubocký; David Janák; Ctibor Povýšil; Jaroslav Lindner (Case Reports in Vascular Medicine)
Objective. To report on a very rare case of a glomus tumor manifested on the upper arm in a healthy young male patient. Case Presentation and Intervention. A 22-year-old male patient presented with bluish multifocal venous malformation on the left upper arm and was admitted for venous malformation excision. Pain, discomfort, and upper arm paraesthesia had been present for almost 6 years. Ultrasonography revealed septet tumor without blood flow in the subcutaneous region of anterior aspect of the upper arm. A multifocal venous malformation approximately 5–10 mm in diameter was excised. Histological examination showed dilated vascular area with proliferated glomus cells with round nucleus in the wall of dilated vascular structures. Based on histological examination, the final diagnosis was made as “glomangioma.” Conclusion. Histological examination is the only method that can establish final diagnosis. Currently, the only available treatment for this type of tumor is surgical excision.